Society Residential Pattern Of Kaili Da'a In Dombu Village - Burhanuddin, Burhanuddin; Zubaidi, Fuad; Luthfiah, Luthfiah (Applied Engineering and Technology, 2022)
Kaili Da'a, is one of the sub-ethnic Kaili in Central Sulawesi, especially those who live in an area at the foot of the Matantimali Hill in Dombu Village, West Marawola District. In addition to the shape of the house, the arrangement and configuration of residential elements which include community housing, the house of traditional leaders and the existence of bantaya and worship facilities in the form of a church building including different topography and orientation of community housing towards the house of the customary leader is a unique phenomenon to be explored and revealed. 5,53 MW. The objectives to be achieved in this study are to reveal the settlement patterns of the Kaili Da'a community in Dombu Village, identify the factors underlying settlement patterns, and reveal and describe the relationship between the socio-cultural (socio-cultural) factors of the community and settlement patterns. These objectives are studied through the Post Positivistic method with a qualitative approach, in order to reveal the ethical and emotional empiric (not palpable), behind the sensual empiric (physical) of settlements as the focus of this research The settlement pattern of the community or ethnic Kaili Da'a in Dombu Village is based on an orientation towards the east as part of the tradition and culture that has been passed down from generation to generation. Settlement arrangements and facing towards the east are the implementation of the cosmos concept which places nature (macrocosm) as part of human life and dwellings (settlements) as a microcosm (small nature); macrocosmic representation.